Analisis Pengendalian Kualitas Air Minum dalam Kemasan Menggunakan Metode Six Sigma - Widyarto, Wahyu Oktri; Firdaus, Azirwan; Kusumawati, Aulia (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2019)
Bottled drinking water is market with a variety of packaging, one of which is gallon packaging. Some of the problems that occur in the quality of the gallon are leaky gallons, broken gallons, dirty water, dirty bodies, and mossy gallons. This study aims to determine the company's baseline performance as seen from the value of Defect Per Million Opportunities (DPMO) and sigma level, identifying the causes of product defects. Discussions were carried out following DMAIC's steps on six sigma. Based on the results of data processing, it can see that the DPMO value is 662.46, and the sigma level is 4.84. This result can be the basis for the company to improve the performance of the quality of the products produced.